An Empirical Analysis of Progressive Value and Risk of Exploration in the Plutonic Marymia Gold Belt,Western Australia - M Fallon (The Australasian Institute of Mining and Metallurgy, 2009)
The full history of exploration successes, failures and related costs from initial greenfield exploration in 1987 to the current brownfield stages was analysed for the Plutonic Marymia Gold Belt of Western Australia. This belt, which had escaped the attention of turn-of-the-century prospectors and had not produced any gold until 1990, is an ideal area for a collectively exhaustive, progressive value and risk case study of expected return on gold exploration. The study analyses the progressive screening of over 200 greenfield and near mine prospects, through various stages of exploration to the establishment of 38 mining sites, ranging from a few large mines to small satellite operations. It provides empirical estimates of the historical Bayesian probability of projects advancing to successive stages of exploration, eg from reconnaissance, to systematic drill testing, resource delineation, feasibility and mine development, given a successful outcome in any exploration phase. The ratio between the estimated value of the gold discovered and the corresponding historical exploration expenditure in each year and cumulatively, ie the average cost of discovery per ounce of gold, are then computed as measures of historical return on the exploration investment in this belt. These, together with an estimate of the æresidualÆ gold endowment, ie of the number and size of possible as yet undiscovered deposits, generated through the use of rank statistics (ie ZipfÆs law), provide a basis for future strategic consideration in exploration targeting in this and similar geological terranes.